PENGARUH METODE ICE BREAKING DAN MEDIA POSTER TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN IPA DI KELAS III SD NEGERI PEUREUMEU - Rita Oktavia; Nurlaili; Cut Atika Sari (LPPM Universitas Cipta Mandiri, 2025)
This research aims to determine the influence of the ice breaking method and poster media on student’s interest learning science in class III at Peureumeu State Elementary School and to find out how much influence the ice breaking method and poster media have on student’s interest in learning science in class III at Peureumeu State Elementary School. This type of research uses quasi-experiment. The approach in this research uses a quantitative approach. The population in this study were all class III students at Peureumeu State Elementary School, totaling 26 student’s. The data collection techniques used in this research are observation, tests, questionnaires and documentation. The instruments used to collect data in this research consisted of observation sheets, test sheets, questionnaires and validation sheets. The results of this research can be concluded that the first variable (X1), namely ice breaking, has no effect on student’s interest in learning. This is proven based on the calculation of t count < t table (1,191 < 2.068). Poster media (X2) has no effect on student’s interest in learning. This is proven based on the calculated t < t table (-1.326 < 2.068). So it can be concluded that there is no significant influence of the use of the ice breaking method and poster media on student’s interest in learning.